Perhelatan Seni dalam Bingkai Dinamika Zaman Taman Balekambang Surakarta (1921-2020) - Rudy Wicaksono Herlambang; Rahmanu Widayat; Galih Pranata (Mudra Jurnal Seni Budaya, 2021)
Balekambang Park is one of the many tourist objects that are quite popular in the Solo area. Not only does it present the beauty of the garden, but also keeps a long historical side. This paper seeks to record flashbacks of art events from time to time that have occurred in Taman Balekambang Surakarta. The results showed that Balekambang Park was once busy with a variety of art performances and the enthusiasm of the audience until the 80s before being displaced by the globalization media which made Balekambang Park lose its crowd and began to be abandoned in the 90s. Whereas previously, various art events such as WOP, Kethoprak had triumphed in the 80s. This alarming condition is increasingly felt where Balekambang Park has begun to be viewed with a negative stigma with the establishment of the night world in it and other dark sides such as 'plus-plus' massage and so on. Revitalization efforts were then carried out by the Solo City Government starting from the revitalization by Solo City Leaders Joko Widodo and FX Rudy in 2008. In addition, the establishment of new facilities such as the Open Stage is an effort to preserve Balekambang Park while maintaining the existence of art and cultural events that have been held in the Park since long ago.